Humans [plural] in the loop: the forgotten collective aspects of privacy, consenting, controlling, and digital protection - Soheil Human; Soheil Human; Soheil Human (Frontiers in Political Science)
The integration of digital technologies into various aspects of life is not only transforming industries and economies but also fundamentally altering human interactions and societal dimensions, raising critical ethical and societal concerns, particularly regarding human agency and human rights. Current approaches for addressing these concerns, particularly in the case of digital privacy, are predominantly “individual-centric”, placing an undue burden on individuals who often lack the necessary knowledge and resources to protect their digital rights. This article argues for a paradigm shift toward human-compatible approaches by providing individuals with cognitive, collective, and contextual supports to empower them. The article redefines “humans in the loop” as a collective practice and expands the ongoing debates from “data protection” to the broader discourse of “digital protection.” It proposes the establishment of novel sociotechnical mechanisms, such as the “Advanced Data Protection Control (ADPC)”, within internet infrastructures to facilitate effective communication between users and stakeholders. This approach addresses the shortcomings of current practices dominated by service providers and advocates for innovative policy-making and technical advancements. By integrating collective supports with automation and other cognitive and contextual supports, the goal is to foster a sustainable and accountable digital future that ensures pluralism, inclusion, and human agency in the continuous co-creation, evaluation, and improvement of digital technologies.